Fluoroplastic film with UV blocking effect and preparation method thereof

By using inorganic UV absorbers in fluoroplastic films, the problem of degradation of smoke and UV absorption capacity in high-temperature processing and long-term use of organic UV absorbers is solved, and efficient UV barrier effect and long-life film performance is achieved.

CN119752072APending Publication Date: 2025-04-04SHANGHAI FUJIA NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510251611.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing fluoroplastic films will produce smoke when using organic UV absorbers during high-temperature processing, and the UV absorption capacity will decrease due to poor compatibility with polymer organic matter during long-term use.

Method used

Using inorganic UV absorbers, materials such as titanium dioxide, alumina, zinc nitrate hexahydrate, cerium oxide and sodium silicate are prepared through specific processes to form nano-scale inorganic UV absorbers and disperse them evenly in fluoroplastic film.

Benefits of technology

Inorganic UV absorbers effectively block UV light through dual mechanisms of reflection and absorption, improving the UV barrier effect and service life of fluoroplastic films, while also having excellent light, thermal and chemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752072A_ABST
    Figure CN119752072A_ABST
Patent Text Reader

Abstract

The present invention relates to a fluoroplastic film with UV blocking effect and a preparation method thereof, and belongs to the technical field of fluoroplastic films. The fluoroplastic film of the present invention is formed by mixing and melting fluoroplastic particles and an inorganic UV absorber and then casting the film. The inorganic UV absorber undergoes a multi-step complex preparation process, including grinding, dissolving, ultrasonication, roasting and other steps to obtain excellent UV blocking performance; the film preparation process includes the steps of mixing and melting fluoroplastic particles and inorganic UV absorber, extruding, casting and cooling, wherein the parameters such as mixing, stirring, drying and casting are all optimized. The fluoroplastic film prepared by the present invention has excellent UV blocking effect and is suitable for various occasions requiring UV protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluoroplastic films and relates to a fluoroplastic film with UV blocking effect and a preparation method thereof. Background Art

[0002] Fluoroplastic is a polymer containing fluorine atoms in the molecular chain. Because fluorine atoms have very high electronegativity, fluoroplastics have excellent chemical resistance, flame retardancy and long-term outdoor weather resistance. Fluoroplastic films made from fluoroplastics are often used in places with high outdoor weather resistance requirements, such as photovoltaic module front panels, back panels, membrane structure buildings, and building exterior wall protective films. Fluoroplastic films themselves have excellent UV transmittance. When used as an outer protective film, UV rays can penetrate into the underlying materials, causing the underlying materials to turn yellow and the strength to decrease. In order to solve the problem of yellowing and performance degradation of the underlying materials, it is necessary to add UV absorbing additives to the fluoroplastic film so that UV rays will not penetrate into the underlying materials, thereby achieving the purpose of long-term outdoor protection.

[0003] The prior art is to add an organic UV absorber to fluoroplastics, such as benzophenone, benzotriazole and triazine UV absorbers. The specific steps are to pre-mix fluoroplastic particles and UV absorbers with a high-speed mixer, add the mixed raw materials to a twin-screw extruder for high-temperature melt mixing and granulation to obtain fluoroplastic particles with UV absorption function, and add the fluoroplastic particles with UV absorption function to a cast film extruder to obtain a fluoroplastic film with UV absorption function through cast molding.

[0004] However, a large amount of smoke will appear during the high-temperature processing of the organic UV absorber, because the organic UV absorber will undergo a small amount of degradation during the high-temperature melting process, resulting in smoke; subsequently, during long-term use, because the organic UV absorber is a small-analyte organic substance and has poor compatibility with high-molecular organic substances, precipitation (surface frosting) will occur during long-term use, resulting in a decrease in UV absorption capacity. Therefore, the present invention realizes the function of UV absorption by selecting a suitable inorganic UV absorber. Summary of the invention

[0005] The purpose of the present invention is to provide a fluoroplastic film with UV blocking effect and a preparation method thereof, which has the characteristics of good UV blocking effect.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A fluoroplastic film with UV blocking effect, wherein the fluoroplastic film is formed by mixing fluoroplastic particles and an inorganic UV absorber and then casting the mixture into a film, wherein the inorganic UV absorber is prepared by the following method: S1.1: titanium dioxide and aluminum oxide were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 800 r / min for 1-2 h to obtain a mixture A; S1.2: Dissolve zinc nitrate hexahydrate in deionized water to obtain a zinc nitrate solution with a concentration of 0.5-1 M, add mixture A to the zinc nitrate solution to obtain a solid-liquid mixture with a solid-liquid mass ratio of 1:1 g / mL, slowly heat the solid-liquid mixture to 40°C, maintain the temperature for 0.5-1 h, and filter and dry to obtain mixture B; S1.3: Mix mixture B and cerium oxide in a mass ratio of 1: (0.5-1), add 1wt% citric acid, put into a ball mill and grind at a speed of 500r / min for 0.5h to obtain a solid mixture, calcine the solid mixture at 500℃ for 2h, and grind it after cooling to obtain mixture C; S1.4: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 3-5%, mixture C and hydrotalcite are mixed in a mass ratio of 1:1, and the mixture is added to the sodium silicate solution to obtain a solid-liquid mixture with a solid-liquid mass ratio of 1:(2-3) g / mL, ultrasonically treated for 1-2 h, and filtered to obtain mixture D; S1.5: Freeze the mixture D in liquid nitrogen for 10 to 15 minutes, dry it at -70 to -50°C under vacuum for 4 to 6 hours, and after freeze-drying, grind it to obtain the inorganic UV absorber.

[0007] Furthermore, the particle size of the mixture A in S1.1 is 500 mesh.

[0008] Furthermore, the rate of slow heating in S1.2 is 2°C / min.

[0009] Furthermore, the drying parameters in S1.2 are: drying temperature 80° C., and drying time 12 h.

[0010] Furthermore, the inorganic UV absorber obtained by crushing and grinding in S1.5 has a particle size of 800 mesh.

[0011] A process for preparing a fluoroplastic film with UV blocking effect, wherein the specific steps of the process for preparing the fluoroplastic film are as follows: S6.1: Mix fluoroplastic particles and inorganic UV absorber in a mass ratio of 1:1, put into a mixing mixer after mixing evenly, heat to 190-210°C under a nitrogen atmosphere to make the mixture molten, then add 1 wt% dispersant, continue stirring for 2 h, and obtain mixture E; S6.2: Under nitrogen atmosphere, the mixture E is passed through a die, cooled and shaped, and pelletized to obtain a mixed masterbatch, which is then placed in a dryer for drying; S6.3: Put the dried mixed masterbatch into an extruder, cast and cool, let stand for 12 hours, and roll up and package the finished product to obtain the fluoroplastic film.

[0012] Furthermore, the rotation speed of the mixing stirrer in S6.1 is 800 r / min.

[0013] Furthermore, the dispersant in S6.1 is polyethylene glycol, and the number average molecular weight is 2000.

[0014] Furthermore, the drying parameters in S6.2 are: drying temperature 80-90° C., and drying time 3-4 hours.

[0015] Furthermore, the thickness of the fluoroplastic film obtained by casting in S6.3 is 25 μm.

[0016] The inorganic nano UV absorber prepared by the present invention can block UV light through the dual mechanism of reflection and absorption, and has a high blocking efficiency: (1) Shielding effect of reflection or scattering. When ultraviolet rays hit inorganic particles, their surface can disperse ultraviolet rays and play a blocking role. Nano-scale particles, whose particle size is smaller than the wavelength of ultraviolet rays, can emit electromagnetic waves in all directions and scatter ultraviolet light.

[0017] (2) Absorption, solid energy band theory, these inorganic particles are generally wide bandgap semiconductors. When exposed to high-energy ultraviolet rays, the electrons in the valence band are excited and jump to the conduction band, and hole-electron pairs are generated at the same time. When excited, the electrons absorb energy, thereby reducing the direct exposure to ultraviolet rays.

[0018] The inorganic UV absorber of the present invention is prepared through a specific process and can absorb ultraviolet rays more effectively, thereby reducing the damage of ultraviolet rays to the fluoroplastic film. By uniformly dispersing the inorganic UV absorber in the fluoroplastic film, the resistance of the film to ultraviolet rays can be improved and the service life of the film can be extended. The active ingredients in the inorganic UV absorber prepared by the present invention can absorb ultraviolet rays and convert ultraviolet energy into harmless heat energy or other forms of energy through physical or chemical processes, thereby preventing ultraviolet rays from damaging the fluoroplastic film. Moreover, through processes such as ball milling and ultrasound, the inorganic UV absorber is uniformly dispersed in the fluoroplastic film, avoiding agglomeration, thereby improving its ultraviolet absorption efficiency and stability.

[0019] The present invention adopts inorganic substances as the main components. The absorbent has excellent light, heat and chemical stability. No toxic or harmful substances are used in the preparation process, and the absorbent meets environmental protection standards.

[0020] Titanium dioxide has excellent photocatalytic properties and strong oxidizing properties. It is one of the key ingredients for preparing UV absorbers. Titanium dioxide has strong blocking and absorption capabilities for ultraviolet rays. When ultraviolet rays hit the surface of titanium dioxide particles, part of the ultraviolet rays will be reflected back and part will be absorbed by titanium dioxide. The absorbed ultraviolet rays will undergo energy conversion inside the titanium dioxide particles or be released in the form of heat, thus avoiding further damage to the material by ultraviolet rays; aluminum oxide has high hardness, high melting point and high chemical stability, which can enhance the wear resistance and corrosion resistance of the absorber. Aluminum oxide can maintain structural integrity in high temperature environments and is not easy to decompose. As a component of inorganic UV absorbers, inorganic UV absorbers can withstand certain mechanical stress and thermal stress during processing and use. During the preparation process and subsequent applications, aluminum oxide can exist stably and will not undergo adverse chemical reactions with other components. The performance of the entire inorganic UV absorber is affected. Alumina is not easy to decompose at high temperatures and can form a good interface with other ingredients such as titanium dioxide, further enhancing the thermal stability of the mixture. Zinc nitrate hexahydrate can provide zinc ions, which will be adsorbed on the surface or pores of titanium dioxide and alumina to form a modified layer containing zinc ions. Therefore, the introduction of zinc ions can change the surface charge state and electronic structure of the matrix material, thereby enhancing its ability to absorb ultraviolet rays. Zinc ions form chemical bonds or coordination bonds with oxygen atoms in matrix materials such as titanium dioxide and alumina, thereby enhancing the overall structural stability of the material. This interaction will also cause the band structure of the matrix material to change, thereby changing its response characteristics to ultraviolet rays. In addition, the presence of zinc ions increases the material's absorption cross-section for ultraviolet rays, allowing more ultraviolet rays to be absorbed by the material, and then by promoting the electron transition or energy transfer process inside the material, the material's absorption and conversion efficiency for ultraviolet rays is enhanced; cerium oxide has excellent redox properties, which helps to improve the light stability and catalytic activity of the absorber, and cerium oxide has good absorption of ultraviolet rays. When ultraviolet rays irradiate cerium oxide, it can effectively absorb the energy of these ultraviolet rays, thereby reducing the impact of ultraviolet rays on the material. The invention discloses a method for preparing the inorganic UV absorber and the method for preparing the inorganic UV absorber. The method comprises the steps of: firstly, using sodium silicate as a bonding agent, and secondly, using sodium silicate as a bonding agent, and then using sodium silicate as a bonding agent to bond inorganic particles such as titanium dioxide, aluminum oxide, and cerium oxide firmly together to form a compact structure, thereby improving the mechanical strength and durability of the inorganic UV absorber. The addition of sodium silicate can also improve the absorption and scattering ability of the inorganic UV absorber to ultraviolet rays. The silicate colloid formed by the sodium silicate and the metal ions has a large specific surface area and porosity, and can more effectively capture and fix ultraviolet rays. The invention also adds citric acid as a performance improver, and the multiple hydroxyl and carboxyl groups contained in the sodium silicate can be complexed with metal ions such as zinc ions and cerium ions to form a stable complex. This complexation not only helps to prevent the aggregation and precipitation of metal ions during the grinding process, but also improves the performance of the final product.

[0021] The present invention mixes fluoroplastic particles and inorganic UV absorbers in a mass ratio of 1:1, heats them to a molten state, and then adds a dispersant for stirring, thereby ensuring that the raw materials are evenly mixed, which is beneficial to improving the UV blocking effect and overall performance of the film. The entire preparation process is carried out under a nitrogen atmosphere, which can effectively prevent the raw materials from reacting with oxygen in the air during the heating and melting processes, thereby preventing the film performance from decreasing or generating undesirable by-products. The casting process is used for cooling and molding, which can achieve continuous production and improve production efficiency. It is also beneficial to control the thickness and width of the film and ensure the stability of product quality. Due to the addition of the inorganic UV absorber, the fluoroplastic film has an excellent UV blocking effect, can effectively prevent ultraviolet rays from damaging the internal materials of the film, and prolong the service life of the film. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.

[0023] Figure 1 The invention discloses a preparation process of the fluoroplastic film. DETAILED DESCRIPTION

[0024] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.

[0025] Example 1 The fluoroplastic film is formed by mixing fluoroplastic particles and an inorganic UV absorber and then casting the mixture into a film by melting. The inorganic UV absorber is prepared by the following method: S1.1: titanium dioxide and aluminum oxide were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 800 r / min for 1.5 h to obtain a mixture A, wherein the particle size of the mixture A was 500 mesh; S1.2: Dissolve zinc nitrate hexahydrate in deionized water to obtain a zinc nitrate solution with a concentration of 1 M, add mixture A to the zinc nitrate solution to obtain a solid-liquid mixture with a solid-liquid mass ratio of 1:1 g / mL, slowly heat the solid-liquid mixture to 40°C at a rate of 2°C / min, ultrasonicate for 1 h after constant temperature, filter, and dry at 80°C for 12 h to obtain mixture B; S1.3: Mix mixture B and cerium oxide in a mass ratio of 1:1, add 1wt% citric acid, put into a ball mill and grind at a speed of 500r / min for 0.5h to obtain a solid mixture, calcine the solid mixture at 500℃ for 2h, and crush it after cooling to obtain mixture C; S1.4: Sodium silicate was dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 5%, mixture C and hydrotalcite were mixed in a mass ratio of 1:1, and the mixture was added to the sodium silicate solution to obtain a solid-liquid mixture with a solid-liquid mass ratio of 1:2 g / mL, and ultrasonicated for 2 h, and filtered to obtain mixture D; S1.5: The mixture D is frozen in liquid nitrogen for 15 minutes, dried at -70°C under vacuum for 4 hours, and after freeze-drying, crushed and ground to obtain the inorganic UV absorber with a particle size of 800 mesh.

[0026] The specific steps of the fluoroplastic film preparation process are as follows: S6.1: Mix fluoroplastic particles and inorganic UV absorber in a mass ratio of 1:1, mix well and put into a mixer, the speed of the mixer is 800 r / min, heat to 200°C under nitrogen atmosphere to make the mixture molten, add 1 wt% polyethylene glycol 2000, continue stirring for 2 h, and obtain mixture E; S6.2: Under nitrogen atmosphere, the mixture E is passed through a die, cooled and shaped, and pelletized to obtain a mixed masterbatch, and the mixed masterbatch is placed in a dryer for drying. The drying parameters are drying temperature 90° C. and drying time 3 h. S6.3: Put the dried mixed masterbatch into the extruder, cast and cool, let it stand for 12 hours, and roll up and package the finished product to obtain the fluoroplastic film, the thickness of the fluoroplastic film is 25 μm.

[0027] Example 2 The fluoroplastic film is formed by mixing fluoroplastic particles and an inorganic UV absorber and then casting the mixture into a film by melting. The inorganic UV absorber is prepared by the following method: S1.1: titanium dioxide and aluminum oxide were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 800 r / min for 1 h to obtain a mixture A, wherein the particle size of the mixture A was 500 mesh; S1.2: Dissolve zinc nitrate hexahydrate in deionized water to obtain a zinc nitrate solution with a concentration of 0.5 M, add mixture A to the zinc nitrate solution to obtain a solid-liquid mixture with a solid-liquid mass ratio of 1:1 g / mL, slowly heat the solid-liquid mixture to 40°C at a rate of 2°C / min, ultrasonicate for 0.5 h after constant temperature, filter, and dry at 80°C for 12 h to obtain mixture B; S1.3: Mix mixture B and cerium oxide in a mass ratio of 1:0.5, add 1wt% citric acid, put into a ball mill and grind at a speed of 500r / min for 0.5h to obtain a solid mixture, calcine the solid mixture at 500℃ for 2h, and crush it after cooling to obtain mixture C; S1.4: Sodium silicate was dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 3%, mixture C and hydrotalcite were mixed in a mass ratio of 1:1, and the mixture was added to the sodium silicate solution to obtain a solid-liquid mixture with a solid-liquid mass ratio of 1:3 g / mL, and ultrasonicated for 1 h, and filtered to obtain mixture D; S1.5: The mixture D is frozen in liquid nitrogen for 10 minutes, dried at -50°C under vacuum for 6 hours, and after freeze-drying, crushed and ground to obtain the inorganic UV absorber with a particle size of 800 mesh.

[0028] The specific steps of the fluoroplastic film preparation process are as follows: S6.1: Mix fluoroplastic particles and inorganic UV absorber in a mass ratio of 1:1, mix well and put into a mixer, the speed of the mixer is 800 r / min, heat to 190°C under nitrogen atmosphere to make the mixture molten, add 1 wt% polyethylene glycol 2000, continue stirring for 2 h, and obtain mixture E; S6.2: Under nitrogen atmosphere, the mixture E is passed through a die, cooled and shaped, and pelletized to obtain a mixed masterbatch, and the mixed masterbatch is placed in a dryer for drying. The drying parameters are: drying temperature 80° C., and drying time 4 h; S6.3: Put the dried mixed masterbatch into the extruder, cast and cool, let it stand for 12 hours, and roll up and package the finished product to obtain the fluoroplastic film, the thickness of the fluoroplastic film is 25 μm.

[0029] Example 3 The fluoroplastic film is formed by mixing fluoroplastic particles and an inorganic UV absorber and then casting the mixture into a film by melting. The inorganic UV absorber is prepared by the following method: S1.1: titanium dioxide and aluminum oxide were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 800 r / min for 2 h to obtain a mixture A, wherein the particle size of the mixture A was 500 mesh; S1.2: Dissolve zinc nitrate hexahydrate in deionized water to obtain a zinc nitrate solution with a concentration of 1 M, add mixture A to the zinc nitrate solution to obtain a solid-liquid mixture with a solid-liquid mass ratio of 1:1 g / mL, slowly heat the solid-liquid mixture to 40°C at a rate of 2°C / min, ultrasonicate for 0.5h after constant temperature, filter, and dry at 80°C for 12h to obtain mixture B; S1.3: Mix mixture B and cerium oxide in a mass ratio of 1:1, add 1wt% citric acid, put into a ball mill and grind at a speed of 500r / min for 0.5h to obtain a solid mixture, calcine the solid mixture at 500℃ for 2h, and crush it after cooling to obtain mixture C; S1.4: Sodium silicate was dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 3-5%, mixture C and hydrotalcite were mixed in a mass ratio of 1:1, and the mixture was added to the sodium silicate solution to obtain a solid-liquid mixture with a solid-liquid mass ratio of 1:3 g / mL, and ultrasonicated for 2 h, and filtered to obtain mixture D; S1.5: The mixture D is frozen in liquid nitrogen for 10 minutes, dried at -70°C under vacuum for 6 hours, and after freeze-drying, crushed and ground to obtain the inorganic UV absorber with a particle size of 800 mesh.

[0030] The specific steps of the fluoroplastic film preparation process are as follows: S6.1: Mix fluoroplastic particles and inorganic UV absorber in a mass ratio of 1:1, mix well and put into a mixer, the speed of the mixer is 800 r / min, heat to 210°C under nitrogen atmosphere to make the mixture molten, add 1 wt% polyethylene glycol 2000, continue stirring for 2 h, and obtain mixture E; S6.2: Under nitrogen atmosphere, the mixture E is passed through a die, cooled and shaped, and pelletized to obtain a mixed masterbatch, and the mixed masterbatch is placed in a dryer for drying. The drying parameters are drying temperature 90° C. and drying time 3 h. S6.3: Put the dried mixed masterbatch into the extruder, cast and cool, let it stand for 12 hours, and roll up and package the finished product to obtain the fluoroplastic film, the thickness of the fluoroplastic film is 25 μm.

[0031] Comparative Example 1 In this comparative example, titanium dioxide is not added in the preparation of the inorganic UV absorber, and the remaining steps are consistent with those in Example 1.

[0032] Comparative Example 2 In this comparative example, aluminum oxide was not added during the preparation of the inorganic UV absorber, and the remaining steps were consistent with those of Example 1.

[0033] Comparative Example 3 In this comparative example, zinc nitrate hexahydrate was not added in the preparation of the inorganic UV absorber, and the remaining steps were consistent with those in Example 1.

[0034] Comparative Example 4 In this comparative example, cerium oxide was not added during the preparation of the inorganic UV absorber, and the remaining steps were consistent with those of Example 1.

[0035] Comparative Example 5 In this comparative example, no sodium silicate was added during the preparation of the inorganic UV absorber, and the remaining steps were consistent with those of Example 1.

[0036] The performance of the fluoroplastic film was tested on Examples 1 to 3, and the experimental results are summarized in the following table:

[0037] The UV blocking rate and tensile strength of Example 1 and Comparative Examples 1 to 5 were tested, and the experimental results are summarized in the following table:

[0038] Experimental data show that the addition of titanium dioxide, aluminum oxide, zinc nitrate hexahydrate, cerium oxide and sodium silicate in the preparation of inorganic UV absorbers can effectively improve the performance of fluoroplastic films.

[0039] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A fluoroplastic film with UV blocking effect, characterized in that: The fluoroplastic film is formed by mixing fluoroplastic particles and an inorganic UV absorber and then casting the mixture into a film. The inorganic UV absorber is prepared by the following method: S1.1: titanium dioxide and aluminum oxide were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 800 r / min for 1-2 h to obtain a mixture A; S1.2: Dissolve zinc nitrate hexahydrate in deionized water to obtain a zinc nitrate solution with a concentration of 0.5-1 M, add mixture A to the zinc nitrate solution to obtain a solid-liquid mixture with a solid-liquid mass ratio of 1:1 g / mL, slowly heat the solid-liquid mixture to 40°C, maintain the temperature for 0.5-1 h, and filter and dry to obtain mixture B; S1.3: Mix mixture B and cerium oxide in a mass ratio of 1: (0.5-1), add 1wt% citric acid, put into a ball mill and grind at a speed of 500r / min for 0.5h to obtain a solid mixture, calcine the solid mixture at 500℃ for 2h, and grind it after cooling to obtain mixture C; S1.4: Sodium silicate is dissolved in deionized water to obtain a sodium silicate solution with a mass fraction of 3-5%, mixture C and hydrotalcite are mixed in a mass ratio of 1:1, and the mixture is added to the sodium silicate solution to obtain a solid-liquid mixture with a solid-liquid mass ratio of 1:(2-3) g / mL, ultrasonically treated for 1-2 h, and filtered to obtain mixture D; S1.5: Freeze the mixture D in liquid nitrogen for 10 to 15 minutes, dry it at -70 to -50°C under vacuum for 4 to 6 hours, and after freeze-drying, grind it to obtain the inorganic UV absorber.

2. A fluoroplastic film with UV blocking effect according to claim 1, characterized in that: The particle size of the mixture A in S1.1 is 500 mesh.

3. The fluoroplastic film with UV blocking effect according to claim 1, characterized in that: The rate of slow heating in S1.2 is 2°C / min.

4. The fluoroplastic film with UV blocking effect according to claim 1, characterized in that: The drying parameters in S1.2 are: drying temperature 80° C., and drying time 12 h.

5. The fluoroplastic film with UV blocking effect according to claim 1, characterized in that: The particle size of the inorganic UV absorber obtained by crushing and grinding in S1.5 is 800 mesh.

6. A process for preparing a fluoroplastic film with UV blocking effect, based on the fluoroplastic film with UV blocking effect as claimed in any one of claims 1 to 5, characterized in that: The specific steps of the fluoroplastic film preparation process are as follows: S6.1: Mix fluoroplastic particles and inorganic UV absorber in a mass ratio of 1:1, put into a mixing mixer after mixing evenly, heat to 190-210°C under a nitrogen atmosphere to make the mixture molten, then add 1 wt% dispersant, continue stirring for 2 h, and obtain mixture E; S6.2: Under nitrogen atmosphere, the mixture E is passed through a die, cooled and shaped, and pelletized to obtain a mixed masterbatch, which is then placed in a dryer for drying; S6.3: Put the dried mixed masterbatch into an extruder, cast and cool, let stand for 12 hours, and roll up and package the finished product to obtain the fluoroplastic film.

7. A process for preparing a fluoroplastic film with UV blocking effect according to claim 6, characterized in that: The rotating speed of the mixing stirrer in S6.1 is 800 r / min.

8. The process for preparing a fluoroplastic film with UV blocking effect according to claim 6, characterized in that: The dispersant in S6.1 is polyethylene glycol, and the number average molecular weight is 2000.

9. The process for preparing a fluoroplastic film with UV blocking effect according to claim 6, characterized in that: The drying parameters in S6.2 are: drying temperature 80-90° C., and drying time 3-4 hours.

10. The process for preparing a fluoroplastic film with UV blocking effect according to claim 6, characterized in that: The thickness of the fluoroplastic film obtained by casting in S6.3 is 25 μm.

Citation Information

Patent Citations

  • Solar cell encapsulating film and preparation method thereof

    CN103214770A

  • High-concentration white master batch for polyvinylidene fluoride (PVDF) films and production method thereof

    CN104059317A

  • Polyacrylate modified polyvinylidene fluoride film with excellent ultraviolet resistance and preparation method thereof

    CN108084613A

  • Photovoltaic polyvinylidene fluoride membrane as well as preparation method and application thereof

    CN115558224A